2021
DOI: 10.3390/pathogens10050515
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Liquid and Volatile Fractions of Essential Oils against Biofilm Formed by Selected Reference Strains on Polystyrene and Hydroxyapatite Surfaces

Abstract: Biofilms are surface-attached, structured microbial communities displaying higher tolerance to antimicrobial agents in comparison to planktonic cells. An estimated 80% of all infections are thought to be biofilm-related. The drying pipeline of new antibiotics efficient against biofilm-forming pathogens urges the search for alternative routes of treatment. Essential Oils (EOs), extracted from medicinally important plants, are a reservoir of bioactive compounds that may serve as a foothold in investigating novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 89 publications
2
8
0
Order By: Relevance
“…In our study, liquid fractions of TT-EO emulsions exerted antibiofilm effect in concentration ranges from 6.3 to 0.8% ( v/v ) ( Table 3 ). These results are consistent with results of our previous studies in which we observed that liquid fractions of the EOs are able to reduce viability of staphylococcal biofilm cells in microdilution assays [ 50 , 53 ]. Feng et al have indicated complete removal of mature MRSA biofilm after the exposure to 0.32% TT-EO [ 62 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, liquid fractions of TT-EO emulsions exerted antibiofilm effect in concentration ranges from 6.3 to 0.8% ( v/v ) ( Table 3 ). These results are consistent with results of our previous studies in which we observed that liquid fractions of the EOs are able to reduce viability of staphylococcal biofilm cells in microdilution assays [ 50 , 53 ]. Feng et al have indicated complete removal of mature MRSA biofilm after the exposure to 0.32% TT-EO [ 62 ].…”
Section: Discussionsupporting
confidence: 93%
“…Tween 20 was used as non- ionic surfactant to enhance solubilization and reduce evaporation of EOs [ 52 ]. According to our previous research, addition of 0.5% ( v/v ) Tween 20 improved anti-staphylococcal activity of TT-EO liquid fractions [ 53 ]. As it is presented in Figure S1 in Supplementary Materials , Tween 20 did not inhibit growth of S. aureus planktonic cells in the concentrations used for emulsion preparation.…”
Section: Discussionmentioning
confidence: 99%
“…EOs were diluted using Tween 20 (0.5%, v / v ) [ 45 ] at the following concentrations 0.5, 0.25, 0.15, and 0.1% ( v / v ) and filtered using sterilized nylon syringe filters (0.22 µm). The antimicrobial activity was assessed by a standard disc diffusion assay [ 46 ].…”
Section: Methodsmentioning
confidence: 99%
“…Recently, the antimicrobial action of essential oils (EOs) has been of interest to some researchers. 27 Dudek-Wicher et al studied the antibiofilm efficacy of 3 essential oils: tea tree, geranium and frankincense essential oils, incorporated in BC against Gram-positive (S. aureus spp., Enterococcus faecalis spp.) and Gram-negative (Klebsiella pneumoniae spp., P. aeruginosa spp., E. coli spp.)…”
Section: Essential Oilsmentioning
confidence: 99%
“…All tested EOs exhibited antibiofilm efficacy against the tested strains, with efficacy of nearly 80-100%, exhibited by tea tree and geranium essential oils. 27 Unlike antiseptics or antibiotics, the volatile property of EOs allows them to reach the areas neighboring the areas of application. Bacterial cellulose enriched with thymol, a component of an essential oil, was successfully applied on a third-degree burn wound closure.…”
Section: Essential Oilsmentioning
confidence: 99%